Conhecimento para docência de futuros professores de Matemática: o estudo de aula no estágio supervisionado - Roselene Alves Amâncio (2023)
This thesis is the result of research aimed at understanding the knowledge for teaching constructed by future Mathematics teachers when participating in a Lesson Study during supervised curricular internship. Additionally, it aims to identify the perceptions of future teachers regarding the Lesson Study. We conducted collaborative research, developing the Lesson Study with two interns from the Mathematics Teaching program, with occasional participation from the supervising teacher. The interns attended thirteen meetings with the researcher for the development of the Lesson Study, and these sessions were recorded, transcribed, and textualized. Individual interviews were also conducted at the end of the internship to understand their perceptions of the Lesson Study in which they participated. We chose to organize and analyze the data by relevant themes for mathematics teaching that proved to be more prominent, selecting some episodes that occurred during the meetings. Our investigation highlights that participation in the Lesson Study during the internship allowed the interns to construct interconnected mathematical and curricular knowledge, involving different aspects of the mathematics teaching and learning process (justification, different types of tasks, communication, instructional materials), as well as knowledge related to classroom dynamics. It also shows that the interns considered that Lesson Study enriched the internship experience in several aspects, among which we highlight: studying articles focused on the mathematics classroom; the collective and reflective work that involved preparing classes, preparing detailed lesson plans, conducting and analyzing classes; learning related to mathematics teaching and classroom dynamics.